Perlindungan Hukum Terhadap Anak Dalam Konflik Bersenjata di Suriah - Imam Rokhyani (UIN Sunan Kalijaga Yogyakarta, 2018)
The armed conflict in Syria began in March 2011and has murdered many victims and millions of peoplehave fled. During the conflict that occurred during theArab Spring in the Middle East region, there wereindications of infractions of Geneva Convention IV1949. The infractions lead into violence acts involvingchildren in, such as murdering, torturing, sexualviolence and recruiting them into the organization ofarmed groups. Besides breaking the GenevaConventions, those actions are in contradiction with oneof the principles of international humanitarian law, i.e.the distinction principle. This paper discusses the legalprotection of children in armed conflict, in Syria, inaccordance with the Geneva Convention IV of 1949 andthe relevant regulations.